Pemeriksaan Tinggi Potensi Genetik dan Length Increments Balita Stunting - Lina Nurbaiti; Deasy Irawati; Ardiana Ekawanti; Rifana Cholidah (Jurnal Gema Ngabdi, 2019)
One in four children in the world are stunted. The process of growth and development in the children under five years is a process that is very important in determining the future of the child both physically, mentally and behaviorally. Genetic ability can appear optimally if it is supported by a conducive environmental factor, which is meant by environmental factors is nutrient intake. Stunting is a national and even global issue and Sukadana Village, Teruwai, is one of the stunting village loci established by the government. Through early detection and knowing of problems with the child's development, the recovery can be done earlier, so that the child's growth and development can take place optimally. Early detection of cases of stunting children under five years by examination of high genetic potential and length increments. The results of the analysis revealed that 12 toddlers whose TB / U were normal in the first month (60%) but whose BB / U increase decreased in the following month would be at risk of stunting if nutritional intake was not heeded. While 36 toddlers with TB / U diagnosed with stunting can be estimated to have stunted due to malnutrition, only 2 toddlers who are short due to familial short stature and 2 toddlers are likely to be stunting due to endocrine. Based on this data it can be seen what more appropriate intervention is given for stunting toddler cases. Length increments evaluated every 3 months are the best screening indicators for stunting events. There is no relationship between parental height and the incidence of stunting